Diagnosis and management of idiopathic condylar Resorption: A review of literature - Yasser S. Alali; Khaled M. Al Habeeb; Khaled A. Al Malhook; Sami Alshehri (Saudi Dental Journal)
Background and objectives: Idiopathic condylar resorption (ICR) can be described as a dysfunctional remodeling of the temporomandibular joint (TMJ). It is clinically characterized by morphological changes in TMJ including reduced ramus height, accelerated mandibular retrusion and reduced growth in juveniles. With a strong predilection towards females (90 %) within an age group of 10 to 40 years, diagnosis and management of ICR is a critical clinical challenge. The aim of this study is to present a comprehensive review of diagnosis and management strategies for ICR. Materials and Methods: Literature search based on keywords relating to ICR was conducted on PubMed (Medline) database. Studies fulfilling the inclusion criteria (reports based on clinical diagnosis and management of ICR) were selected for comprehensive review. Results: 253 articles were identified through literature search. After abstract screening and full-text review, 54 studies were selected for qualitative synthesis. Diagnosis of ICR is established by combination of clinical and radiographic findings, patient history, and exclusion of all known local/systemic factors contributing to condylar resorption. Management of ICR depends on condylar activity and surgeon’s ability to preserve the articular disc and mandibular condyle, and could either be surgical or non-surgical. Surgical treatment can be either by orthognathic surgery alone or through a combination of orthognathic and TMJ surgeries. Conclusion: Based on the present review, it may be concluded that diagnosis and management of ICR requires adequate clinical understanding of the condition. Identifying the stage of ICR is important in deciding optimum treatment plan. While early-stage ICR could be managed non-surgically by orthodontic and splint therapies, advanced stage disease require simultaneous TMJ Surgery with orthognathic correction for skeletal stability. Future research should focus on elucidating underlying mechanisms of ICR, refining diagnostic criteria, and optimizing treatment protocols to enhance patient outcomes.